Autologous Hematopoietic Stem Cell Transplantation for Chronic Inflammatory Demyelinating Polyradiculoneuropathy. (26th November 2021) - Masson-Roy, Josée; Breiner, Ari; Warman-Chardon, Jodi; Pringle, Catherine E.; Allan, David; Bredeson, Christopher; Huebsch, Lothar; Kekre, Natasha; Kennah, Michael Lee; Martin, Lisa; McDiarmid, Sheryl; Altouri, Sultan; et al.
ABSTRACT: Background: Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) refractory to conventional therapy can lead to marked disability and represents a therapeutic challenge. Objective: To report five cases of treatment-refractory disabling CIDP treated with autologous hematopoietic stem cell transplantation (AHSCT). Methods: This was a retrospective cohort study from a tertiary care referral center for both neuromuscular disease and AHSCT. Patients with CIDP treated with AHSCT between 2008 and 2020 were included. All patients had major persistent and disabling neuropathic deficits despite combinations of intensive immunosuppressive therapy. The primary outcome measures were: Medical Research Council sum score, Overall Neuropathy Limitations Scale and requirement for ongoing CIDP immunotherapy after transplantation. We also analyzed safety outcomes by documenting all severe AHSCT-related complications. Results: Five patients with refractory CIDP underwent AHSCT. Three were classified as manifesting a typical syndrome, two were classified as the multifocal Lewis Sumner variant. The mean age at time of CIDP diagnosis was 33.4 years (range 24–46 years), with a median delay of 46 months (range 21–135 months) between diagnosis and AHSCT. The median follow-up period was 41 months. All five patients were able to wean off CIDP-related immunotherapy. Marked improvements in Medical Research Council scale and overall Neuropathy Limitations Scale were noted in 4/5 patients. One patient with longstanding neurogenic atrophy showed no improvement in disability scales. There were no treatment-related deaths or critical illnesses. Conclusions: AHSCT can achieve marked sustained clinical improvement of refractory CIDP and may allow for weaning off long-term complex immunotherapies.